2010
DOI: 10.1007/s10483-010-0307-z
|View full text |Cite
|
Sign up to set email alerts
|

Multi-objective optimization design of radar absorbing sandwich structure

Abstract: By introducing a dimensionless parameter to couple the two objectives, weight and radar absorbing performance, into a single objective function, a multi-objective optimization procedure for the radar absorbing sandwich structure (RASS) with a cellular core is proposed. The optimization models considered are one-side clamped sandwich panels with four kinds of cores subject to uniformly distributed loads. The average specular reflectivity calculated with the transfer matrix method and the periodic moment method … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 22 publications
(24 reference statements)
0
9
0
Order By: Relevance
“…However, in TM polarization, the −10 and −9 dB absorption bandwidth rarely change with the incident angle increased ( Figure 6B). The reflectivity is smaller than −8 dB in the full band (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18) and in the five chosen tested incident angles. Thus, the incident angle threshold of effective absorption for CFRMM in TM polarization is larger than 60 .…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…However, in TM polarization, the −10 and −9 dB absorption bandwidth rarely change with the incident angle increased ( Figure 6B). The reflectivity is smaller than −8 dB in the full band (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18) and in the five chosen tested incident angles. Thus, the incident angle threshold of effective absorption for CFRMM in TM polarization is larger than 60 .…”
Section: Resultsmentioning
confidence: 95%
“…Microwave absorbing materials (MAM) play an important role in electromagnetic compatibility, electromagnetic battle, and stealth technology. [1][2][3][4] Recently, more and more researchers take interests in the properties of MAM and exertion of their microwave absorbing (MA) potential. In view of the application of MAM coatings, they not only need to exhibit small reflection over a large frequency range, but also should be mechanically resistant in harsh environment.…”
Section: Introductionmentioning
confidence: 99%
“…The experiments suggested that honeycomb panels of 18 mm and 20 mm thickness have a better performance in radar absorption than the panels with 13 mm thickness. This method was also applied by Chen et al to make radar‐absorbing lattice grids. Square‐honeycomb and triangular‐honeycomb structures were studied including the role of cell dimension and panel thickness.…”
Section: Modern Honeycombsmentioning
confidence: 99%
“…Chen et al . reported a lightweight microwave absorbing structure with two dimensional composite lattice cores, which can be regarded as an effective absorber with a wider absorption band 15 . Kim et al .…”
Section: Introductionmentioning
confidence: 99%